Factors Related to Over-waist Circumference and Overweight among Nurses in Phichit Hospital - Khiewkhern, Santisith; Teerawattanasak, Phongpan (Journal of Health Science of Thailand, 2017)
Over-waist circumference and overweight are associated with metabolic syndrome which is prone to myocardia infraction and stroke. Nurses might risk to over-waist circumference and overweight due to characteristics of their jobs. The objective of this study was to investigate factors related to over-waist circumference and overweight among nurses. It was conducted in Phichit Hospital, Phichit Province. Study participants were nurses aged 35 years old and over who had worked in the hospital for at least 6 months. Data were collected by using questionnaire and health examination records; and were analized by using frequency distribution, mean, standard deviation, independent t-test, odds ratio and Chi-square test. There were 187 nurses participating in the study. It was found that nurses with over-waist circumference had approximately 2 times higher proportion of the late-night meal than those with normal waist circumference (OR=1.96, 95%CI=1.07-3.58). In addition, the late-night meal was statistical significantly associated with over-waist circumference in nurses (p<0.05). The overweight group was more proportion of the late-night meal around 2 times than those who were not overweight (OR=1.81, 95%CI=1.01-3.26). In addition, the late-night meal was statistical significantly associated with overweight in nurses (p<0.05). Therefore, nurses should be concerned about the appropriate calories and nutrition of the late-night meal.